Reskilling and Upskilling: HR Adaptation Strategies to Digital Transformation in the Traditional Sector - Eko Winarni; Siti Mujannah; Abdul Halik; Pardomuan Pardosi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Digital transformation forces the traditional sector to adapt through reskilling and upskilling as a human resource development strategy. The sector faces a major challenge in ensuring employees have digital skills relevant to new technologies. This study aims to analyze the effectiveness of reskilling and upskilling training strategies in improving employee digital readiness in the traditional sector. The research method uses a quantitative descriptive approach through a survey of 150 respondents involved in the training program. The data was analyzed using descriptive and inferential statistical analysis to evaluate the relationship between the type of training, the duration of the training, and the level of digital readiness of employees. The results showed that information technology training dominated with 40% of respondents, followed by project management training by 30%. The majority of short-duration training (1-3 months) is effective in improving employees' digital readiness, but less attention is paid to developing soft skills. This gap points to the need for a more holistic approach to training. The conclusion of the study confirms that the combination of technical training and soft skills is essential to support digital transformation as a whole. Quality, relevant, and continuous training is the key to the success of human resource adaptation in the traditional sector. This research suggests an inclusive and strategic training policy to accelerate the digital transformation process.